Looking back, looking forward: taking stock of teacher education at (another) crossroad. Issue 1 (1st January 2022) - Reid, Jo-Anne; Hall, Graeme
ABSTRACT: Teacher education in the time of the covid is unpredictable indeed. Fifty years ago, a major political overhaul of initial teacher education removed control from state education departments and began the transition of ITE to a university discipline. This led to the emergence of the teacher education professional, and the need for an association such as ATEA to maintain self-regulation and development of the field. While "on the ground" the daily practice of teacher education may not feel the same as it did in 1971, when we think about our possible futures, we argue that we must always take account of our pasts – and how they have shaped the social, political, and educational contexts we do and will experience. The things we do as teacher educators, along with how we do them, where we do them, and even who we do them with, are always changing: attention to our history is essential as we imagine shaping our future. We are indeed in an unpredictable position. We revisit our history here to argue that there is benefit now, in listening to advice from the past – and considering the possibilities of a road not yet taken.